Analysis of Possible Attacks on Data and Possible Solutions with Comparative Analysis of Various Encryption Algorithms and Evaluation (International Journal of Innovative Research in Engineering & Management, 2022)
Today's fast-growing technology, "Cloud  computing," is widely employed in various industries  because to its low-cost services, such as pay-per-use mode,  which allows users to access resources via an Internet  connection. Cloud storage is a service offered by cloud  service providers that allows users to store their data on a  remote server. Although cloud service providers ensure that  data kept in the cloud will be safe and secure, there are a  number of issues that must be addressed. For user data in  the cloud, data integrity and security must be assured. The  integrity of the data must be unmistakable. There are some  security dangers associated with storing sensitive data with  cloud storage companies. The lack of data integrity is a big  worry in the cloud environment. Encryption computations  are used to provide complete security of data being sent  from one source to another, as well as to prevent private  data from being exposed to unauthorized parties.  Encryption computations are mostly useful for obtaining  and protecting information being sent from one end to the  next from any type of flaw. Some of these computations  have been adopted by scientists to ensure data security in  banking, healthcare, and the military. When used for  information security, a fraction of these computations are  varied in terms of effectiveness, exactness, dependability,  and reaction time. We considered Rivest-Shamir-Adleman  (RSA), Advanced Encryption Standard (AES),  BLOWFISH, and Data Encryption Standard (DES) calculations in order to conduct a relative evaluation.  Because there is scepticism about which of the  computations is more reliable, trustworthy, and practical  when considering the highlights that depicted their variety. As a result, this work aims to conduct a close examination  of each encryption calculation in order to determine the  optimal method for employing the specified measures.  Python was used to implement modify BLOWFISH's  algorithm. When the results are compared to other  algorithms results, it is discovered that BLOWFISH takes  the shortest time to encrypt, while RSA and AES take the  longest. In addition, based on the measurements used in the  evaluation, the BLOWFISH calculation is regarded as the  most proficient of the three calculations. In this study, only  a few of the obtained results are discussed.
Keywords: Cloud Computing; Security; Algorithms